Work on Sustainability - Ikerd, John (Problemy Ekorozwoju, 2023)
I want to focus my future work on restoring capitalism and reclaiming democracy. Our government has lost the consent of the governed and thus lacks the "just power" to govern, which it must have to restrain rampant economic extraction and exploitation of nature and society.